A case study on the development of an ontology for maintenance services of heavy machinery electronic components - Oliveira, Luiza Bartels; Araujo, Marco Antonio; Dantas, Mario Antonio (Companion Proceedings of the Latin-American Symposium on Dependable and Secure Computing (LADC); 2023: Companion Proceedings of the 12th Latin-American Symposium on Dependable Computing, 2023)
Inadequate data organization within a company can result in decreased efficiency, increased costs, and longer delivery times. In the context of an electronic maintenance laboratory servicing a mining company internally, the lack of data organization hampers the conversion of information into actionable knowledge, affecting delivery efficiency. This study aims to address these issues by transforming existing data into structured knowledge using the Methontology and OntoForInfoScience methodologies. The ontology model was validated by both experts and a software plug-in and seeks to offers a systematic representation of the domain, facilitating data understanding and utilization, ultimately leading to cost and time savings in deliveries and ongoing process improvements.